2012
DOI: 10.1007/s00424-012-1161-4
|View full text |Cite
|
Sign up to set email alerts
|

On the different roles of AT1 and AT2 receptors in stretch-induced changes of connexin43 expression and localisation

Abstract: Cyclic mechanical stretch (CMS) and angiotensin II (ATII) play an important role in cardiac remodelling. Thus, we aimed to examine how ATII affects CMS-induced changes in localisation and expression of the gap junction protein connexin43 (Cx43). Neonatal rat cardiomyocytes cultured on gelatin-coated Flexcell cell culture plates were kept static or were exposed to CMS (110 % of resting length, 1 Hz) for 24 h with or without additional ATII (0.1 μmol/L). Moreover, inhibitors of ATII receptors (AT-R) were used (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Loss of N-cadherin reduces Cx43 expression at gap junctions (Li et al, 2008;Li et al, 2005;Palatinus et al, 2011;Zhu et al, 2010). As cyclic stretch increases N-cadherin in cardiomyocytes, it also increases total Cx43 expression and polarization of Cx43 to the longitudinal sites (Salameh et al, 2012). The increases in Cx43 expression and localisation to gap junctions in stretched cardiomyocytes involve angiotensin II, Akt, Erk1/2 and glycogen synthase kinase (GSK) 3ß (Salameh et al, 2012;Salameh et al, 2010a;Salameh et al, 2010b;Shyu et al, 2001).…”
Section: Regulation Of Cx43 In Heart and Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of N-cadherin reduces Cx43 expression at gap junctions (Li et al, 2008;Li et al, 2005;Palatinus et al, 2011;Zhu et al, 2010). As cyclic stretch increases N-cadherin in cardiomyocytes, it also increases total Cx43 expression and polarization of Cx43 to the longitudinal sites (Salameh et al, 2012). The increases in Cx43 expression and localisation to gap junctions in stretched cardiomyocytes involve angiotensin II, Akt, Erk1/2 and glycogen synthase kinase (GSK) 3ß (Salameh et al, 2012;Salameh et al, 2010a;Salameh et al, 2010b;Shyu et al, 2001).…”
Section: Regulation Of Cx43 In Heart and Cnsmentioning
confidence: 99%
“…As cyclic stretch increases N-cadherin in cardiomyocytes, it also increases total Cx43 expression and polarization of Cx43 to the longitudinal sites (Salameh et al, 2012). The increases in Cx43 expression and localisation to gap junctions in stretched cardiomyocytes involve angiotensin II, Akt, Erk1/2 and glycogen synthase kinase (GSK) 3ß (Salameh et al, 2012;Salameh et al, 2010a;Salameh et al, 2010b;Shyu et al, 2001). Angiotensin II also increases Cx43 expression (Dodge et al, 1998;Polontchouk et al, 2002) and N-cadherin expression in cardiomyocytes (Adam et al, 2010).…”
Section: Regulation Of Cx43 In Heart and Cnsmentioning
confidence: 99%
“…It is worthwhile to note that continual folding/unfolding of the ID membranes may sustain high expression levels of Cx43 in the GJ (and perinexii). Accumulating evidence shows that repeated stretching of the membranes enhances Cx43 expression in neonatal rat cardiomyocytes [32]. Therefore, it is safe to consider that this scenario applies to the adult heart in that an ongoing and intermittent load on the GJ (and perinexii) may sustain high expression levels of Cx43 in the GJ (and perinexii) by promoting electronic conduction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cell axis orientation depended on the stretch axis [50]. The effects of a cyclic mechanical stretch can be modulated by angiotensin II (Salameh et al, 2012) [51] and by alpha-and beta-adrenoceptor stimulation (Salameh et al, 2010a) [52]. Figure 1 summarizes the effects of cyclic mechanical stretch on the localization of cardiac gap junctions.…”
Section: Regulation Of the Localization Of Gap Junction Channelsmentioning
confidence: 99%
“…ACE-inhibitor therapy reduced AF-induced fibrosis (Boldt et al, 2006) [80]. Further investigations in cultured cardiomyocytes revealed that the stretch-induced self-organization of cells with cell elongation and polarization of Cx43 could be modulated by angiotensin II: angiotensin II enhanced Cx43 expression via AT(1)-receptors but reduced Cx43 polarization via AT(2)-receptors (Salameh et al, 2012) [51]. Regarding the underlying mechanism, angiotensin II seems to activate CTGF via the activation of Rac1 and nicotinamide adenine dinucleotide phosphate oxidase.…”
Section: Gap Junction Remodeling In Atrial Fibrillation (Af)mentioning
confidence: 99%